Latihan fisik pada anak penderita asma: Studi literatur - Siti Rahmawati; Iwan Shalahuddin; Gusgus Ghraha Ramdhanie (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Children with asthma and physical exercise: A literature StudyBackground: Physical exercise in children with asthma is very important, but the negative perception that there will be a recurrence of asthma attacks after physical exercise makes them reluctant to do physical exercise. This has a negative impact on fitness which will cause the rate of recurrence of asthma to increase so there will be an increase in the number of emergency management and hospitalizations, followed by poorly attended rates in school, and decreased productivity.Purpose: To synthesize existing research on various physical exercises in children with asthma.Method: This literature design uses a narrative review method. Search for articles specified in Indonesian, namely